Role of Serials in Sci-Tech Libraries - Mount, Ellis (Routledge, 2020)
This book, first published in 1983, examines the key role that serials play in sci-tech libraries, serials being a source of prime importance for scientists and engineers. The problems and costs associated with the selection, handling and storage of serials are closely analysed by expert library specialists.